Cytomegalovirus‐Associated CD4+CD28null Cells in NKG2D‐Dependent Glomerular Endothelial Injury and Kidney Allograft Dysfunction. Issue 4 (26th February 2016) - Shabir, S.; Smith, H.; Kaul, B.; Pachnio, A.; Jham, S.; Kuravi, S.; Ball, S.; Chand, S.; Moss, P.; Harper, L.; Borrows, R.
Abstract : Emerging data suggest that expansion of a circulating population of atypical, cytotoxic CD4 + T cells lacking costimulatory CD28 (CD4 + CD28 null cells) is associated with latent cytomegalovirus (CMV) infection. The purpose of the current study was to increase the understanding of the relevance of these cells in 100 unselected kidney transplant recipients followed prospectively for a median of 54 months. Multicolor flow cytometry of peripheral blood mononuclear cells before transplantation and serially posttransplantation was undertaken. CD4 + CD28 null cells were found predominantly in CMV‐seropositive patients and expanded in the posttransplantation period. These cells were predominantly effector‐memory phenotype and expressed markers of endothelial homing (CX3CR1) and cytotoxicity (NKG2D and perforin). Isolated CD4 + CD27 − CD28 null cells proliferated in response to peripheral blood mononuclear cells previously exposed to CMV‐derived (but not HLA‐derived) antigens and following such priming incubation with glomerular endothelium resulted in signs of endothelial damage and apoptosis (release of fractalkine and von Willebrand factor; increased caspase 3 expression). This effect was mitigated by NKG2D‐blocking antibody. Increased CD4 + CD28 null cell frequencies were associated with delayed graft function and lower estimated glomerular filtration rate at end follow‐up. This study suggests an important role for this atypical cytotoxic CD4 + CD28 null cell subset in kidney transplantation and points to strategies that may minimize the impact on clinical outcomes. Abstract : This prospective study shows the importance of cytomegalovirus in the genesis of atypical cytotoxic CD4 cells, highlighting the in vitro endothelial toxicity and in vivo relationships with inferior early‐ and medium‐term kidney allograft function. See the companion article from Espinosa et al onpage 1102, and the editorial from Murakami and Riella (page 1045 ).